Pengaruh Media Sosial Instagram dan Content Marketing Terhadap Keputusan Pembelian Pada Kopi Uwak - Agesti, Nicky Dwi; Isyanto, Puji; Sumarni, Neni (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
Finding out how social media and content marketing affect customer decisions is the aim of this study. For this validated quantitative investigation, online questionnaires sent using Google Forms were used to gather primary data. This sampling approach employs a sample of 120 respondents and combines a non-probability sampling methodology with purposeful sampling. Following the usage of questionnaires for data collection, IBM SPSS 25 software was used for data analysis. On the other side, content marketing significantly and favorably influences consumers' choices to buy. Additionally, with a value of 26.1%, Instagram social media and content marketing work together to positively and significantly influence consumers' decisions to purchase Uwak Coffee.